BEYOND THE SCREEN: GENDERED DYNAMICS IN ONLINE AND TEXT MESSAGING COMMUNICATION - Nora ACHILI (Ziglôbitha)
Abstract: This paper on gender differences in digital communication is explicitly centered around the use of the Internet and SMS texting to argue that gendered language, styles of communication, and interaction patterns juxtapose men's and women's paths within the complexities of the virtual communication. It positions and relates various fundamental theories on gender and communication from the transition of traditional to computer-mediated channels of interaction in empirical studies conducted by Labov (1972, 1990), Trudgill (1972, 1974), Tannen (1994, 1997), and Cameron (1997, 1998), among others. The discussion gives a specific account of the peculiar ways that men and women use language, which was discovered to be different in previous studies that explained online interaction styles. This article will also trace the transition of computer-mediated communication (CMC) from what was earlier seen as a liberatory, gender-trademark-free space to a medium that, in effect, reproduces real-world social structures and gender inequalities. It also relates to the issue of cultural influences on Internet use, bringing out disparities in different regions regarding access to technology and usage patterns. This article argues that, notwithstanding advanced digital technology, gendered communication practices have found their way into online and mobile interactions. Such a digital gender divide reflects wider social structures, calling into question the neutrality of online media in early works. This result should highlight the critical need for a re-evaluation of digital communication as a tool for social equality, thereby underscoring the call for further research to help untangle the complex intersections underlying gendered technology and communication in the digital era. Keywords: Gender differences, digital communication, Internet studies, SMS texting, sociolinguistics, computer-mediated communication, cultural influence.